Interpretation of Communism and Post-Communist Transformations in Russia: Modern Theoretical Discussions - Vladimir A. Gutorov (Peoples’ Friendship University of Russia (RUDN University), 2021)
The analysis of discussions on various aspects of the evolution of the modern state, the specifics of post-communist transformations and the role that Marxism and the tradition of radical socialist thought can play in the near future in their search for a way out of the crisis generated by the agony of the neoliberal global world order. As a starting point for the analysis, theoretical articles published in the second edition of the collection Communism, Anticommunism, Russophobia in post-Soviet Russia. 2nd ed., Add. / Auth.: P.P. Apryshko et al. - Moscow: World of Philosophy, Algorithm, 2021 (607 p.) were selected. A comparative analysis of the polemical works of domestic scientists, political theorists and philosophers with those discussions that for many decades have been conducted by their colleagues abroad clearly indicates that today none of the existing ideologies, as well as the paradigms of economic and socio-political theory, can pretend to be the only recourse. The experience of recent decades clearly excludes the very possibility of transforming the economy and society on the basis of a certain universal synthetic model. In post-communist Russia, the heat of political passions, which stimulates the extreme polarization of political programs for overcoming the crisis, also hinders the achievement of agreement and the search for a solution acceptable to all.